Return from retail banking and payments - Iftekhar Hasan; Heiko Schmiedel; Liang Song (Bank of Finland, 2010)
The European banking industry joined forces to achieve a fully integrated market for retail payment services in the euro area: the Single Euro Payments Area (SEPA). Against this background, the present paper examines the fundamental relationship between retail payment business and overall bank performance. Using data from across 27 European markets over the period 2000 2007, we analyse whether the provisions of retail payment services are reflected in improved bank performance, using accounting ratios and efficiency measures. The results confirm that banks perform better in countries where the retail payment service markets are more highly developed, and the relationship is stronger in countries with a relatively high adoption of retail payment transaction technologies. Retail payment transaction technology can itself also improve bank performance, and statistical evidence shows that heterogeneity in retail payment instruments is associated with enhanced bank performance. Similarly, a higher usage of electronic retail payment instruments seems to stimulate banking business. We also show that retail payment services have a more significant impact on savings and cooperative bank performance, although they do also have a positive influence on the performance of commercial banks. Additionally, our findings reveal that the impact of retail services on bank performance is dominated by fee income. Finally, an effective payment service market is found to be associated with higher bank stability. Our findings are robust to different regression specifications. The results may also be informative for the industry when reconsidering its business models in the light of current financial market developments
URN:NBN:fi:bof-20140807566
Keywords: 330